The contribution of international financial reporting standards in treating the impact of inflation on the financial statements -analytical study to opinions of accountants and auditors in constantine - - ouadi, roukia (Milev Journal of Research and Studies, 2016)
This research aims to highlight the role played by the International financial reporting standards, in addressing the impact of inflation on the financial statements, by focusing on the Statement of financial position and income statement, so that was addressed to the accounting methods to modify the terms of these lists, which are affected by inflation To achieve the objectives of the study, the questionnaire was used and it was distributed to a sample of Accountants and accounts Governors in Constantine and the Statistical program Spss was used to address the questionnaire . It was reached that these methods despite the technical differences adopted by each method but it gave the new, and added to the accounting principles of some amendments which took into account the change in the general level of prices, and thus made the elements of financial statements evaluating the new way despite the fact that these methods has not been excluded from the principle of historical cost.